Eksistensi Amal Usama Muhammadiyah - Muhammad Maulana Mas'udi (Al Hikmah, 2020)
Muhammadiyah Tambaksari Charity Business focuseson primary and secondary education council (Dikdasmen) is one of the supporting components of Muhammadiyah organizations. The main task of the Primary Education Council is in the field of education, ideally the main task and function is as a community service to pursue formal education. As well as having an important role in fostering the Autonomous Organization (Ortom) in Tambaksari, namely Hizwul Wathon as a scouting organization, Ikatan Pelajar Muhammadiyah(IPM) as a student organization and Tapak Suci as a pancak silat or martial arts organization.This study used data collection methods, interviews and literature study. The results of this study indicated the public's response to the Primary and Secondary Education Council (Dikdasmen) established a charity in the form of educational institutions, namely SD Muhammadiyah 3 Surabaya and SMP Muhammadiyah 13 Surabaya. In this case the community respond positively to the existence of educational charities. First, seeing the development of the number of students in the two Muhammadiyah educational institutions was increasing every year, this also increases public trust. Second, from the results of the interviews with the parents, they decided to send their children to Muhammadiyah educational institutions because there are many excellent programs, such as the Al-Quran tahfidz program. The conclusion of this study was Muhammadiyah educational institutions under the supervision of the Basic Education Council have developed quite well and are able to develop charitable efforts in the field of education to date.